Queering all aboard: challenging the maleness of the leisure boat industry. (4th December 2014) - McIntyre, Magdalena Petersson
The concept boat All Aboard was designed to meet women's expectations of leisure boats. A constellation of firms worked together to find solutions that could lead to business opportunities by challenging the implicit male norms of the leisure boat industry. This article examines the cultural notions of gender and equality that mattered in the process and explores the relationship between bodies, technologies, design, and gender using qualitative ethnographic methods. Based on queer theory, this article argues that ideas of the female body and the female relationship with boats played a significant role in this innovation process. Although invisible (and male) norms masked by so–called neutral designs and technologies were challenged, new norms of what women are like and what it means to be a woman were simultaneously created.